2014
DOI: 10.1002/ajhb.22625
|View full text |Cite
|
Sign up to set email alerts
|

Do physical activity and sedentary behavior relate to cardio‐metabolic risk factor clustering in indigenous Siberian adults?

Abstract: Objectively measured physical activity was related to lower risk of cardio-metabolic risk factor clustering within this sample of Yakut men, but not women. SB was not related to cardio-metabolic indicators. Physical activity may contribute to a reduction in clustering of metabolic risk factors within indigenous circumpolar populations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(13 citation statements)
references
References 64 publications
1
11
1
Order By: Relevance
“…Numerous studies among Indigenous peoples globally and in Brazil have shown an association between physical inactivity and body composition, as measured by BMI or other proxies [23,63,65,[76][77][78]. In the present study, no significant relationship was encountered between physical inactivity and BMI.…”
Section: Discussioncontrasting
confidence: 68%
See 1 more Smart Citation
“…Numerous studies among Indigenous peoples globally and in Brazil have shown an association between physical inactivity and body composition, as measured by BMI or other proxies [23,63,65,[76][77][78]. In the present study, no significant relationship was encountered between physical inactivity and BMI.…”
Section: Discussioncontrasting
confidence: 68%
“…For example, studies using IPAQ instruments show the Inuit in Canada and the Dakota in the United States have physical inactivity rates similar to or below our findings for the Xavante [62,63]. Studies using other methodologies, such as pedometers and other questionnaires, have reported physical inactivity rates above 50 % among Aboriginals and Torres Strait Islanders, Australia and Yakut (Sakha) in Siberia, and predominantly Indigenous urban youth (15 to 23 years) in Ghana [64][65][66][67].…”
Section: Discussionsupporting
confidence: 59%
“…Thirteen papers reported a negative association between sedentary time and HDL‐C (three papers did not adjust for PA and two became non‐significant following adjustment for MVPA ). Fifteen papers reported no significant association between sedentary time and HDL‐C . Sedentary time and low‐density lipoprotein cholesterol (LDL‐C) were positively associated in two papers , neither of which was adjusted for PA. Twelve papers found no significant association between sedentary time and LDL‐C .…”
Section: Resultsmentioning
confidence: 99%
“…From the included papers, 10 came from NHANES , three from AusDiab , three from the Whitehall II Study , two from HSE , two from RISC study and one each from the Generation 100 Study , EVIDENT study , Leuven Longitudinal Study on Lifestyle, Fitness and Health (LLSLFH) , Swedish CArdioPulmonary bioImage Study (SCPIS) , International Physical Activity and the Environment Network Adult Study , New Method for Objective Measurements of Physical Activity in Daily Living study , Hispanic Community Health Study/Study of Latinos and Canadian Health Measures Survey . The remaining 16 papers were all individual/stand‐alone studies . For the meta‐analysis, the aggregated sample size and mean age ( n , years) for the five included health markers were fasting glucose (25,356, 41.6), fasting insulin (10,474, 37.0), triglycerides (26,562, 42.4), HDL‐C (29,582, 46.1) and waist circumference (16,842, 44.6).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation